PENGARUH PENAMBAHAN SARI BUAH NANAS MUDA TERHADAP KARAKTERISTIK FISIK DAN TOTAL BAKTERI TAHU SUSU SAPI - M.H., ARISANDHI; LINDAWATI, S. A.; MIWADA, I N. S. (Fakultas Peternakan Universitas Udayana, 2023)
Milk tofu is a protein product made by adding acid compounds or enzymes to milk, one of which used by adding pineapple juice. This study aim to determine the physical characteristics and total bacteria of cow milk tofu. The design used in this study was a completely randomized design (CRD) with four treatments and four replications, each replication using 1000 ml of cow milk. The four treatments were P1: adding 30 cc of young pineapple juice, P2: adding 40 cc of young pineapple juice, P3: adding 50 cc of young pineapple juice, and P4: adding 60 cc of young pineapple juice. The variables was observed in this study were yield, syneresis, water holding capacity, total acid, and total bacteria. The results showed that adding young pineapple juice had a significant effect (P<0.05) on yield, syneresis, water holding capacity, and total acid, but had no significant effect (P>0.05) on total bacteria of cow milk tofu. The highest yield and water holding capacity of milk tofu was found in P4 with values 21,75% and 73,33% respectively. The lowest syneresis, total acid and total bacteria of milk tofu were found at P4 with values 29,80%, 0,54% and 0,3x104 CFU/g respectively. The conclusion of this study was that adding young pineapple juice had a significant effect on physical characteristics, but had no significant effect on total bacteria. Concentration 60 cc of young pineapple juice produced physical characteristics of cow milk tofu: yield 21,75%, syneresis 29,80%, water holding capacity 73,33%, total acid 0,54%, and total bacteria 0,3x104 CFU/g.